STRUCTURE OF RESONANCE STATES IN THE SIMPLE SCHEMATIC MODEL (International Journal of Mathematics and Physics, 2021)
Many resonant states in the simple schematic two-body model are studied by using complex scaling method. Applying the complex scaling method, we can easily obtain many resonance states even with a wide and a sharp decay widths simultaneously.